РОЛЬ МЕТОДИЧНОЇ РОБОТИ ШКОЛИ У ПІДВИЩЕННІ РІВНЯ ТВОРЧОГО СТИЛЮ ДІЯЛЬНОСТІ ПЕД АГОГА (Педагогіка вищої та середньої школи, 2022)
In the article methodic work at school is being discussed and the advantage of each form of methodic work is shown in connection with the.